2003
DOI: 10.1080/0963828031000137063
|View full text |Cite
|
Sign up to set email alerts
|

The International Classification of Functioning, Disability and Health: a new tool for understanding disability and health

Abstract: Reliable and timely information about the health of populations is part of the World Health Organization's mandate in the development of international public health policy. To capture data concerning functioning and disability, or non-fatal health outcomes, WHO has recently published the revised International Classification of Functioning, Disability and Health (ICF). In this article, the authors briefly outline the revision process and discuss the rationale for the ICF and the needs that it serves in rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
270
0
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(286 citation statements)
references
References 42 publications
2
270
0
14
Order By: Relevance
“…In this vein, this study adopts the exploratory approach of scoping reviews [18] and evaluates qualitative and quantitative studies on psychiatric disability in Africa in order to identify the barriers to and facilitators of employability for individuals with a psychiatric disability as well as existing employment models for persons with psychiatric disabilities in the region. In this study, psychiatric and mental disability are used interchangeably and refer to individuals with a form of mental illness that affects their social and occupational functioning [19]. …”
Section: Introductionmentioning
confidence: 99%
“…In this vein, this study adopts the exploratory approach of scoping reviews [18] and evaluates qualitative and quantitative studies on psychiatric disability in Africa in order to identify the barriers to and facilitators of employability for individuals with a psychiatric disability as well as existing employment models for persons with psychiatric disabilities in the region. In this study, psychiatric and mental disability are used interchangeably and refer to individuals with a form of mental illness that affects their social and occupational functioning [19]. …”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, a disability rate determined by a regional health board, including physicians specialized in related diseases, is taken into account. In addition to the international standards, these measures are used along with the Balthazar formula when assessing the total disability level of an individual (16) . In order to receive disability and nursing care benefits, the disability level of the individual must be at least 50% for them to be evaluated as "severely disabled" by the board.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Little information is available on stroke survivor functioning in SA, particularly at the level of activity limitation (difficulties in task execution) and participation restriction (problems experienced in involvement in life situations). 4 A study in a deprived rural community reported a higher prevalence of stroke survivor disability than expected on the basis of international studies. 5 In another study of patients discharged from a remote rural hospital, 60% had a Modified Rankin Scale (MRS) score of 0 -3 at 3 months and participation in work, social activities, housework and sport was reduced.…”
mentioning
confidence: 99%